Effects on adaptedness of variations in ribosomal DNA copy number in populations of wild barley (Hordeum vulgare ssp. spontaneum). - Zhang, Q F (1990)
Twenty alleles, 12 at Mendelian locus Rrn1 and 8 at locus Rrn2, control rRNA genes [ribosomal DNA (rDNA)] variability in barley. These alleles differ strikingly in their effects on adaptedness. In the present study, we determined variation in the copy number of 101 accessions of wild barley plants from 10 ecologically diverse sites in Israel and examined relationships between rDNA copy number and adaptedness. The average multiplicity of rDNA per haploid genome was 1881 copies and the average numbers of copies for Rrn1 and Rrn2 were 962 and 917, respectively. The total number of copies as well as the number of copies for Rrn1 and Rrn2 varied widely from plant to plant within sites and also from site to site. The predominant allele of Rrn2 had somewhat more copies on the average than the other alleles of this locus but differences between the predominant allele and other alleles of Rrn1 were not statistically significant. Overall, the results indicated that differing amounts of rDNA resulting from variations in copy number and/or number of subrepeats in the intergenic spacer region were not closely associated with adaptedness. This suggests that the high adaptedness of a few specific alleles results in large part from adaptatively favorable nucleotide sequences in the transcription units and/or the intergenic spacer regions of the favored alleles--i.e., that adaptedness in barley depends on the quality more than on the quantity of rDNA present.